Return-to-Work in a Language Barrier Context : Comparing Quebec’s and Ontario’s Workers’ Compensation Policies and Practices - Stephanie Premji; Momtaz Begum; Alex Medley; Ellen MacEachen; Daniel Côté; Ron Saunders (Perspectives Interdisciplinaires sur le Travail et la Santé)
The question of how workers’ compensation systems should account for language barriers is of increasing importance given Canada’s growing linguistic diversity. This study is the first to empirically examine, based on interviews with injured workers and key informants, return-to-work policies and practices through the lens of language barriers. By comparing two jurisdictions, Quebec and Ontario, the study highlights similarities and differences in language accommodation and return-to-work policies and practices that shape the experiences of injured workers with language needs. It argues that gaps in this regard, which are more pronounced in Quebec, contribute to poor return-to-work outcomes for these workers in both provinces.